Service attributes as drivers of behavioral loyalty in casinos: The mediating effect of attitudinal loyalty. (July 2016) - Bilgihan, Anil; Madanoglu, Melih; Ricci, Peter
Abstract: This study takes its cues from the Theory of Reasoned Action (TRA), service quality, and the broaden-and-build theory of positive emotions to investigate the effect of casino service attributes on gambler loyalty. The posited theoretical model was tested using Structural Equation Modeling with a sample of 4511 gamblers. Findings indicate that the intention to return fully mediates the effect of casino ambiance and emotions on return patronage. Feelings pertaining to emotions have the greatest effect on casino players' intention to return. Additionally, emotions have the strongest indirect effect on return patronage. Results highlight the importance of player intent in order to secure their actual return to casinos. In the context of gambling loyalty research, service quality attributes influence return patronage through intention to return. Theoretically, this study shows that attitudinal loyalty is a strong predictor of action loyalty in casinos in a causal fashion. Highlights: A theoretical model was tested using structural equation modeling with a sample of 4511 gamblers. The intention to return fully mediates the effect of casino ambiance and emotions on return patronage. Feelings pertaining to emotions have the greatest effect on casino players' intention to return. Service quality attributes influence return patronage through intention to return. Attitudinal loyalty is a strong predictor of action loyalty.